PEMBUATAN KARBONAT APATIT DARI BAHAN DASAR CANGKANG KEPITING - Jumriana Rahayu Ningsih; Edi Kurniawan (Jurnal Inovasi Teknik Kimia, 2023)
Crab shells are the result of the sea containing calcium and carbonate which combine to form calcium carbonate (CaCO3). The calcium carbonate contained in the crab shells is made into PCC (Precipitation Calcium Carbonate) and CO3Ap (Apatite Carbonate). PCC production in this study used the method of carbonation and carbonate apatite with the dissolution-precipitation reaction. Preparation of apatite carbonate by mixing calcium carbonate derived from crab shells with gypsum and immersing it in a solution of diammonium hydrogen phosphate ((NH4)2HPO4) in the form of blocks with a mass composition of G50P50, G50K50 and G50C50. The resulting Apatite Carbonate Type-B can be proven by the results of FT-IR spectrum analysis. For SEM analysis which showed differences in morphology, distribution and particle size of each block of carbonate apatite.